Clinical relevance of brain atrophy subtypes categorization in memory clinics - Planche, Vincent; Bouteloup, Vincent; Mangin, Jean‐François; Dubois, Bruno; Delrieu, Julien; Pasquier, Florence; Blanc, Frédéric; Paquet, Claire; Hanon, Olivier; Gabelle, Audrey; Ceccaldi, Matthieu; Annweiler, Cédric; et al. (Alzheimer's & dementia, 2021)
Introduction The clinical relevance of brain atrophy subtypes categorization in non‐demented persons without a priori knowledge regarding their amyloid status or clinical presentation is unknown. Methods A total of 2083 outpatients with either subjective cognitive complaint or mild cognitive impairment at study entry were followed during 4 years (MEMENTO cohort). Atrophy subtypes were defined using baseline magnetic resonance imaging (MRI) and previously described algorithms. Results Typical/diffuse atrophy was associated with faster cognitive decline and the highest risk of developing dementia and Alzheimer's disease (AD) over time, both in the whole analytic sample and in amyloid‐positive participants. Hippocampal‐sparing and limbic‐predominant atrophy were also associated with incident dementia, with faster cognitive decline in the limbic predominant atrophy group. Lewy body dementia was more frequent in the hippocampal‐sparing and minimal/no atrophy groups. Discussion Atrophy subtypes categorization predicted different subsequent patterns of cognitive decline and rates of conversion to distinct etiologies of dementia in persons attending memory clinics.